La inteligencia emocional para disminuir conductas agresivas en los niños de preparatoria de la escuela de educación básica Miguel Riofrio de la ciudad de Loja en el periodo 2019-2020. - Bustamante Aguilera, Mabel Stefanía (2020)
The research entitled EMOTIONAL INTELLIGENCE TO DECREASE AGGRESSIVE BEHAVIORS IN CHILDREN OF HIGH SCHOOL OF THE BASQUE EDUCATION SCHOOL MIGUEL RIOFRÍO OF THE CITY OF LOJA IN THE PERIOD 2019-2020; The general objective was to determine how emotional intelligence reduces aggressive behaviors in high school children, in the development of the investigation the methods were used: scientific, synthetic analytical, dialectical, deductive-inductive and statistical-descriptive; for the diagnostic, information was collected from the teacher through an interview; the aggressive behavior checklist of children by the author, Savina Varona, was applied to the parents, and a checklist prepared based on the children was used. to the criteria of the test behavior checklist. The investigated population consisted of sixty-six children, with a sample of a teacher and thirty-three children. The results of the diagnostic made it possible to determine that 52% of the children very frequently manifested aggressive verbal, physical and gestural behaviors. For this, an activity guide called “My world of emotions” was designed and applied. Through the results obtained in the postest, it was evident that aggressive behaviors decreased to 6% of the investigated group, considering that emotional intelligence is an essential aspect to improve social relationships and maintain good coexistence in the classroom.